Dampak Pelaksanaan Program Pengembangan Desa Mitra Di Sentra Pembibitan Sapi Lokal Di Kabupaten Enrekang - Sudirman Baco; Ratmawati Malaka; Zulkharnaim zulkharnaim (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The aim of community service activities carried out in Pattondon Salu Village is to develop the Bali Cattle Breeding Village. This activity is expected to be a stimulus to improve the community's economy. The focus of activities include: 1) the application of farm maintenance management cows and calves, 2) improvement of supporting infrastructure in Cattle Breeding Village and 3) improving health management. The number of farmers contributing to this activity is the Sipakatuo Farmer Group and the Ternak Jaya Farmer Group, with a total of 42 farmers. Data on the progress of the implementation of activities was collected by conducting surveys and interviews using a questionnaire. The collected data is then analyzed descriptively. The results of the implementation of the activities include 1) the number of cattle raised by partners increased from 59 head in 2018 to 79 head in 2019. This increase was due to improved maintenance management; 2) pregnancy cattle increased by 24.53% from 2018 to 69.77% in 2019; and 3) health improvements carried out in the most common diseases found in livestock, namely toxocariasis.